2013
DOI: 10.1038/ejcn.2013.168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various food ingredients on gall bladder emptying

Abstract: Background/objectives:The emptying of the gall bladder in response to feeding is pivotal for the digestion of fat, but the role of various food ingredients in contracting the gall bladder postprandially is not well understood. We hypothesized that different food ingredients, when consumed, will have a different effect on stimulating gall bladder emptying. To investigate this we designed two randomized, investigator-blind, cross-over studies in healthy subjects using magnetic resonance imaging (MRI) to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 47 publications
1
46
0
Order By: Relevance
“…Indeed, this effect was confirmed by the markedly different triglyceride blood profile seen with LE3. These findings are supported by the recent work of Marciani et al (42) who concluded that the amount of fat and its degree of emulsification impact gallbladder secretory function.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, this effect was confirmed by the markedly different triglyceride blood profile seen with LE3. These findings are supported by the recent work of Marciani et al (42) who concluded that the amount of fat and its degree of emulsification impact gallbladder secretory function.…”
Section: Discussionsupporting
confidence: 82%
“…Marciani et al (42) recently highlighted that highly emulsified fat is a potent stimulator of gallbladder emptying. In the current study, the gbv and intestinal fluid content were used to indirectly track the need for such secretions to facilitate digestion.…”
Section: Discussionmentioning
confidence: 98%
“…We selected turmeric, a spice with cultural significance commonly used in Bangladeshi cuisine, because it has a dose-dependent cholekinetic effect; i.e., its active ingredient, curcumin, stimulates gallbladder contraction and thus increases luminal bile acid levels. The effect sizes of turmeric’s cholekinesis vary between reported studies, possibly due to population-based differences (e.g., European versus Asian subjects) or differences in how the spice was administered (Marciani et al, 2013; Rasyid and Lelo, 1999; Rasyid et al, 2002). In a study using serial hydrogen breath tests to assess carbohydrate fermentation and small bowel transit time, investigators observed that turmeric-containing Japanese-style curry fed to Japanese individuals increased fermentation and shortened small bowel transit time compared to curry prepared without turmeric (Shimouchi et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Gall bladder volume was measured pre‐ and postprandial, at every acquisition time point up to 60 minutes postprandially . This was carried out using the same images as for the gastric volumes as previously shown.…”
Section: Methodsmentioning
confidence: 99%